Design Thinking-A New Approach in Patriotic Education - G.B, Mukhanova; N.N, Ashirbayeva; R, Amanbaykyzy; Z.I., Ashimova (Journal of Posthumanism, 2025)
The relevance of the study is that the problem of patriotism education on the basis of creativity is relevant in the current realities of Kazakhstan. Various negative extreme manifestations in the life of Kazakhstanis, leading to an increase in suicides and divorces among the younger generation and in society as a whole, requires new approaches to solving these problems. The article analyses theoretical aspects of studying patriotism on the basis of new approaches, including design thinking. In this regard, this article is aimed at identifying and revealing the essence of this situation and finding new ways and opportunities to create the conditions necessary for a decent life and education of patriotism in Kazakhstan. The purpose of the article is to develop a structural and functional model of education of Kazakhstan patriotism in the conditions of modern realities of Kazakhstan, the development of humanitarian technologies and design-thinking, influencing the formation of New Kazakhstan patriotism. The leading method to the study of this problem is the method of modelling, the method of creative approach, which allows us to consider this problem as a purposeful and organised process to improve the general cultural and human skills they need for effective education of patriotism.